2011
DOI: 10.1111/j.1745-4549.2011.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Aromatic Amines in Meat

Abstract: Heterocyclic aromatic amines (HCAs) are formed during cooking proteinaceous foods such as meat at temperatures above 150C. Epidemiologic studies have shown that all HCAs are mutagenic, and many are carcinogenic. To date, more than 25 HCAs have been identified at ng/g levels in cooked foods. It is therefore recommended minimizing HCAs occurrence in foods consumed by humans. Thus, more information about them is needed. The purpose of this review is to explain chemistry, formation, precursors, mutagenicity and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 99 publications
(137 reference statements)
7
99
4
Order By: Relevance
“…PhIP content in grilled beef can reach levels as high as 38.00 ng g À1 , and similar amounts are found during frying processes (Knize et al, 1995a,b;Oz and Kaya, 2011). The obtained results are consistent with data found in literature concerning PhIP concentration in grilled beef (Oz and Kaya, 2011).…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…PhIP content in grilled beef can reach levels as high as 38.00 ng g À1 , and similar amounts are found during frying processes (Knize et al, 1995a,b;Oz and Kaya, 2011). The obtained results are consistent with data found in literature concerning PhIP concentration in grilled beef (Oz and Kaya, 2011).…”
Section: Resultssupporting
confidence: 95%
“…The analysis of the obtained results shows that the amount of identified AIAs was high for grilled beef. According to data found in literature, 4,8-DiMeIQx content in grilled beef does not exceed 1.20 ng g À1 (Rivera et al, 1996;Alaejos and Afonso, 2011;Oz and Kaya, 2011), MeIQx does not exceed 6.00 ng g À1 (Fay et al, 1997;Alaejos and Afonso, 2011;Oz and Kaya, 2011), MeIQ does not exceed 2.70 ng g À1 (Friedman et al, 2009), and IQ does not exceed 0.50 ng g À1 (Yamaizumi et al, 1986;Alaejos and Afonso, 2011;Oz and Kaya, 2011).…”
Section: Resultsmentioning
confidence: 71%
“…Epidemiological studies have shown that most HCAs are highly mutagenic (Felton et al, 1984) and almost all of them are also carcinogenic (Skog, Johansson, & J€ agerstad, 1998). In comparison to other known food mutagens, HCAs are over 100 fold more mutagenic than aflatoxin B 1 and over 2000 fold more mutagenic than benzo[a]pyrene (Oz & Kaya, 2011a). The International Agency for Research on Cancer (IARC) regards some of the HCAs as possible human carcinogens (MeIQ, MeIQx, PhIP, AaC, MeAaC, Trp-P-1, Trp-P-2 and Glu-P-1 as class 2B carcinogens) and one of them as a probable human carcinogen (IQ, class 2A) (Oz & Kaya, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cooking causes the formation of some chemical compounds that negatively affect health (Oz & Kaya, 2011a). One of these chemical compounds is heterocyclic aromatic amines (HCAs).…”
Section: Introductionmentioning
confidence: 99%
“…Cooking method is another factor for the HCAs formation [56]. Investigations of various cooking methods have shown pan-frying and grilling/ barbecuing to generally yield higher levels of HAAs than oven roasting, deep-fat frying, boiling or microwaving [57,58].…”
Section: +mentioning
confidence: 99%